Ecological study for prioritization of districts of Odisha for swacch bharat mission implementation based on a new modified environmental sanitation index using census 2011 and AHS 2012 data - Kshatri, J. S.; Panda, Manasee; Tripathy, R. M. (International Journal Of Community Medicine And Public Health, 2017)
Background: Open defecation practices and contaminated drinking water are the two major sources of excreta-related infections. Swacch Bharat Mission (SBM) is a cleanliness campaign launched in India in 2014 for duration of five years. Primary Objectives: 1. Determine the effect of open defecation and drinking water sources on the incidence of diarrheal diseases in Odisha. 2. Categorisation of the districts according to a Modified Environmental Sanitation Index (M.E.S.I). Methods: Type of study: Ecological study. Study instrument: Secondary data collected from Census of India-2011 and Annual Health Survey report, 2012. A Modified E.S.I (M.E.S.I.) score was calculated for Odisha using ESI template developed by Balamurugan and Ravichandran. Statistical analyses were done using GNU PSPP Statistical Analysis Software Release 0.9.0. Results: According to the Census of India, 2,129,276 (22.04%) households in Odisha used latrines, including water closet and pit latrines. From the AHS-2012 data it was found that the overall incidence of diarrhea /dysentery in Odisha was 5.92 per 1000 population. Association with diarrheal disease incidence was estimated after classifying districts into 4 categories according to the use of latrines as <10%, 10-20%, 20-30% and >30%. The mean incidence of diarrheal diseases was lower in districts that had higher use of toilets. The variables from each broad category were classified into positive and negative indicators for ESI calculation and MESI score was calculated. Based on the M.E.S.I, the districts were ranked. Dhenkanal, Kandhamal, Nayagarh were ranked worst. Conclusions: Districts should be prioritized based on MESI score for effective SBM implementation.